Analisis Pengembangan Sumber Daya Manusia Dan Locus Of Control Internal Terhadap Kinerja Pegawai Di Pemerintah Kecamatan Sibolga Sambas Kota Sibolga - Fauziah Nur Simamora; Kaharuddin Kaharuddin; Rifka Hadia Lubis; Delita Sihotang (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
The aim of this research is to analyze the influence of HR development and locus of control on the performance of Civil Servants in the Sibolga Sambas District Government, Sibolga City. This research uses a quantitative approach. This research also uses inferential statistics, namely research that aims to explain the position of the variables studied as well as the relationship and influence between other variables. The instruments in this research were questionnaires, interviews and observations. The total population was 160 people including all state civil servants and honorary employees. used are multiple regression tests, t tests, correlation coefficients, and other tests. The R square value obtained was 0.456. The HR Development variable (X2) influences performance by 45.6%, and the remaining 54.4% is determined by other reasons outside the regression model. The regression line equation is Y = 8.169 + 0.197 X1 + 0.615X3. The t test shows that tcount = 6.439 and ttable= 1.654, meaning tcount > ttable = 6.439 > 1.654, it can be concluded that Ha is accepted and H0 is rejected.